2019
DOI: 10.3390/ijerph17010088
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and Vegetable Purchases in Farmer’s Market Stands: Analysing Survey and Sales Data

Abstract: Farmers' market implementation holds promise for increasing access to healthy foods. Although rarely measured, purchase data constitute an intermediate outcome between food environment and actual consumption. In a study conducted with two seasonal Fruits and Vegetables (FV) stands in a disadvantaged area of Montréal (Canada), we analysed how accessibility, perception, and mobility-related factors were associated with FV purchase. This analysis uses a novel measure of FV purchasing practices based on sales data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 79 publications
1
7
0
Order By: Relevance
“…Canadian study was similar to the mean variety in our study (2•8 v. 2•7) (36) . In addition, Freedman et al (37) suggested that an approach that includes the establishment of farmers' markets in low-income neighbourhoods, acceptance of federal food assistance benefits for payment and availability of healthy food incentive programming may increase purchasing at farmers' markets among underserved populations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Canadian study was similar to the mean variety in our study (2•8 v. 2•7) (36) . In addition, Freedman et al (37) suggested that an approach that includes the establishment of farmers' markets in low-income neighbourhoods, acceptance of federal food assistance benefits for payment and availability of healthy food incentive programming may increase purchasing at farmers' markets among underserved populations.…”
Section: Discussionsupporting
confidence: 90%
“…This study also adds to the literature regarding expenditures at farmers' markets: a Canadian study revealed that farmers' market shoppers spent on average $5 CAD (∼$3•60 USD)/trip to the market v. $23/trip in our sample (36) . The mean variety of FV purchased in the Significance at the α < 0•05 level indicated using boldface type.…”
Section: Discussionmentioning
confidence: 60%
“…According to USDA reports, more than 8000 farmers markets are currently listed in the National Farmers Market Directory [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, some research has looked into the issue of noncompliance in the use of weights and measures. A study conducted in Canada by Rebouillat et al (2020) revealed that business people are incapable of using weights and measurement due to difficulties in accessing the measurements, poor individual perceptions on weights and measurements as well as lack of knowledge and awareness on the use of weights and measures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, studies by different scholars (Savio et al, 2016;Filho & Gonçalves, 2015;Yiridoe, 2005) shade light on the role of weights and measures on trade in general. Moreover, other scholars (Ibrahim & Mashenene, 2021;Rebouillat et al, 2020) focused on effects of service quality (SQ) on Weights and Measures customer satisfaction as well as access to weights and measures in business. While a study by Bengesi (2018) studies was slightly connected to the current one, its focus was on factors hindering the use of standard weights and measures along Irish supply chain.…”
Section: Introductionmentioning
confidence: 99%